Analyze the Efficacy of the AST to Platelet Ratio (APRI) and the Fibronectin Fibrinolysis-4 (FIB-4) using Transient Elastography (FIB-SCAN) in Patients with Chronic Hepatitis C - Rehmat Ullah, Kapeel Raja, Sohail Hussain, Zille-Huma, Farhana Mukhtar, Khalil Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to compare the effectiveness of AST to platelet index (APRI) and FIB-4 with transient elastography, also known as fibro scan, in patients who suffered from chronic Hepatitis C. Study Design: Retro-prospective/ Cross-sectional Place & Duration: Khalifa Gulnawaz Teaching Hospital Bannu Pakistan, From August, 2021 to May, 2022. Material and Methods: This research included 360 men and women. After obtaining written consent, detailed demographics of all cases were recorded. In 360 HCV infected individuals, the diagnosis comprised CBC, LFTs, ELISA, PCR, and fibro. We compared AST, apric, FIB-4, and fibro scans for detecting HCV fibrosis progression. SPSS 22.0 was used to analyze all data. Results: There were majority males 220 (61.1%) and 140 (38.9%) females. 85 (23.6%) had age 20-30 years 180 (50%) cases had age 31-40 years and 95 (26.4%) patients had age >40 years. We found that 210 (58.3%) patients had fibrosis stage F0-F1, F2 stage was in 28 (7.8%) cases, F3 stage was in 52 (14.4%) patients and F4 stage in 70 (19.4%) cases. Among 360cases, genotype 3a was found in 260 (72.2%) patients, genotype 1b in 70 (20.8%) cases and genotyped 1a in 30 (8.3%) cases. Conclusion: In this study, we found that the AST to Platelet Index (APRI) and FIB 4 were able to successfully identify among cirrhotic and non-cirrhotic phases among HCV-infected patients. Keywords: Liver, Hepatitis C, Fibrosis